Introducing Restorative Justice in The Criminal Justice System as An Alternative Approach to Addressing the Shoplifting Crisis in Western Australia - Fauzurrahman, Iqbal (Faculty of Law, Universitas Airlangga, 2024)
Abstract This research advocates for the adoption of restorative justice as a more effective response to the escalating shoplifting crisis in Western Australia. The research, centered on the region's unique challenges, employs a conceptual approach, delving into the Rational Choice theory and restorative justice paradigm within the criminal justice system. As shoplifting incidents surge, notably contributing to stock losses for retailers, the study critiques the traditional criminal justice system's limitations and advocates for innovative alternatives. Shoplifting has become a pressing concern in Western Australia, evidenced by rising crime rates and significant stock losses for retailers. The Rational Choice Theory provides a comprehensive framework for understanding shoplifting, emphasizing the calculated decision-making process and socio-economic drivers behind this criminal behavior. The research introduces restorative justice as a viable alternative, emphasizing its success in Western Australia. This community-oriented approach fosters trust and collaboration between law enforcement and retail owners, addressing the limitations of the traditional criminal justice system. Applying the Rational Choice Theory to dissect the step-by-step process of shoplifting, the research acknowledges its relevance while highlighting limitations, such as overlooking non-material motivations. The conclusion emphasizes the Criminal Code's recognition of shoplifting as a crime in Western Australia and underscores the potential of restorative justice programs to mitigate recidivism, prioritize victim satisfaction, and address root causes, offering a more comprehensive and inclusive response to the shoplifting crisis. Keywords: Shoplifting, Restorative Justice, Western Australia Abstrak Penelitian ini meneliti penggunaan restorative justive sebagai respons yang lebih efektif terhadap krisis pencurian ritel di Western Australia. Penelitian ini, berfokus menggunakan pendekatan konseptual dengan menjelajahi Rational Choice Theory dan paradigma Restorative Justice dalam sistem keadilan pidana. Saat insiden pencurian ritel meningkat, yang secara signifikan berkontribusi pada kerugian stok bagi pengusaha, studi ini mengkritisi keterbatasan sistem keadilan pidana tradisional dan menganjurkan inovasi alternatif. Pencurian ritel telah menjadi perhatian mendesak di Western Australia, terbukti oleh peningkatan tingkat kejahatan dan kerugian stok yang signifikan bagi pengecer. Rational Choice Theory memberikan kerangka kerja komprehensif untuk memahami pencurian ritel, menekankan proses pengambilan keputusan yang terhitung dan pendorong sosial-ekonomi di balik perilaku kriminal ini. Penelitian ini memperkenalkan keadilan restoratif sebagai alternatif, terutama pada pendekatan yang berorientasi masyaratkat dengan memupuk kepercayaan dan kerjasama antar penegak hukum dan pemilik ritel mengatasi keterbatasan sistem keadilan pidana tradisional. Dengan menerapkan Rational Choice Theory untuk menganalisis proses langkah demi langkah pencurian ritel, penelitian mengakui relevansinya dan menyoroti keterbatasannya, seperti mengabaikan motivasi non-material. Kesimpulan menekankan pada pengaturan hukum pidana terhadap pencurian ritel sebagai kejahatan di Western Australia dan menyoroti potensi program keadilan restoratif untuk mengurangi kenaikan tindak pidana, mengutamakan kepuasan korban, dan mengatasi akar penyebab, menawarkan respons yang lebih komprehensif dan inklusif terhadap krisis pencurian ritel. Kata Kunci: Pencurian Ritel, Keadilan Restoratif, Western Australia